Mangrove Ecosystem Degradation through Land Conversion in Indonesia’s Coastal Areas: A Review - Apriani Apriani; Delistiani (Yayasan Cipta Anak Bangsa (YCAB) Publisher, 2025)
Background: Mangrove forests are unique plant formations commonly found in protected coastal areas in tropical and subtropical regions. The existence of mangrove forests is essential due to their ecological, economic, and social benefits. Mangroves play a significant role in carbon sequestration, preventing seawater intrusion, reducing erosion and coastal abrasion, acting as natural wave barriers, filtering water, and serving as nursery grounds for various marine species, particularly fish. Objective: This study aims to analyze the factors driving mangrove land conversion in Indonesia's coastal areas and to examine its environmental and socio-economic impacts. Methods: This research employs a literature review approach. Relevant articles were sourced from the PubMed and Google Scholar databases using the keyword